2019
DOI: 10.1183/13993003.01773-2018
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal membrane oxygenation and surgical embolectomy for high-risk pulmonary embolism

Abstract: Patients with high-risk pulmonary embolism (PE) presenting with cardiogenic shock refractory to supportive measures have a high mortality [1, 2]. Therapeutic success depends on rapid haemodynamic stabilisation and restoration of pulmonary blood flow. Thrombolytic therapy is the most widely used recanalisation strategy, but this treatment has substantial drawbacks including a high rate of bleeding complications and limited efficacy in patients with large embolic burden or in patients with recurrent PE presentin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 14 publications
3
35
0
Order By: Relevance
“…ECMO is a rapid and reliable mechanical circulatory support device that decreases RV volume overload (5), and is also recommended as a treatment option for PE patients with refractory circulatory collapse or cardiac arrest. The overall survival rate of patients who receive ECMO for high PE has been reported to be 38-67% (5)(6)(7)(8)19). For patients who required CPR prior to ECMO initiation, the survival rate was only 13-27%, similar to our result (20%).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…ECMO is a rapid and reliable mechanical circulatory support device that decreases RV volume overload (5), and is also recommended as a treatment option for PE patients with refractory circulatory collapse or cardiac arrest. The overall survival rate of patients who receive ECMO for high PE has been reported to be 38-67% (5)(6)(7)(8)19). For patients who required CPR prior to ECMO initiation, the survival rate was only 13-27%, similar to our result (20%).…”
Section: Discussionsupporting
confidence: 87%
“…Veno-arterial extracorporeal membrane oxygenation (ECMO), a temporary mechanical circulatory support device, has been increasingly used over the past 20 years to treat high-risk PE. Several case series studies (5)(6)(7)(8) have demonstrated the potential benefit of ECMO in high-risk PE patients with several indications, including haemodynamic support for profound shock or cardiac arrest, contraindication to systemic thrombolysis, failed reperfusion therapy, and cardiogenic shock after surgical embolectomy.…”
Section: Introductionmentioning
confidence: 99%
“…Our data also demonstrate that peri-operative management has changed throughout the years. In particular, peri-operative veno-arterial (VA) ECMO support has been integrated into the management of PE patients as well as current guideline recommendations 6,14–16 . In our study, ECMO was used in 15 patients; the 30-day survival rate was 60%, which is comparable to the observations of other researchers 16–18 .…”
Section: Discussionsupporting
confidence: 80%
“…Among the 421 studies identified by the search strategy, 106 studies were deemed eligible and 21 studies were eventually included in the analysis, for a total population of 635 patients with acute high‐risk PE receiving ECMO support 11‐31 . Exclusion reasons were: overlapping populations ( n = 10), studies not focused on ECMO use in PE ( n = 4), commentary papers ( n = 3), studies not reporting outcome of interest ( n = 1), and case reports/cases series including < 4 patients ( n = 67).…”
Section: Resultsmentioning
confidence: 99%